Burning birds - Morscheck, Emilie (Moonee Ponds, Vic : H Cox & J Crupi trading as In Short Publishing Company, 2015)
"'Ruthie O'Donnell was saying goodbye forever by slamming the door in my face.' Kicked out of his apartment, Edward sets out on a journey to find his estranged mother, armed with 20 years of unsent letters. In a 300km journey to Sydney the silent shadow that has followed Edward since childhood begins to chip away at his hope for ever finding peace with himself."--Back cover.
Keywords: Missing persons -- New South Wales -- Sydney -- Juvenile fiction; Journey family -- Juvenile fiction; Australian